Pengembangan desain teko set gerabah kontemporer berbasis budaya lokal di Kabupaten Bojonegoro - Kristian Oentoro (Institut Seni Indonesia Yogyakarta, 2019)
Pottery is a type of traditional craft that has taken root in the history of art and culture of the Indonesian society. This fact is supported by various forms of ancient earthenware crafts which discovered since prehistoric times and the emergence of pottery craft centers in various parts of Indonesia, including in Rendeng Village, Malo District, Bojonegoro Regency. The changing of market needs and tastes today are a common problem faced by the traditional craft industry, including pottery crafts. Local wealth inside the traditional handicraft design which increasingly disappearing is one of the common concerns. The development of this contemporary pottery design aims to revive the skills of pottery craftsmen and the local culture of the Bojonegoro society in a modern design style. The research and development produced three sets of earthenware teapots, namely a turtle-shaped teapot set, a white combination of turtle-shaped teapot and teapot set inspired by Bojonegoro local coffee. Design research uses action research methods which consist of three design cycles. The application of this research method is useful to improve the capabilities and creativity of pottery craftmen in designing craft designs. Each design development cycle has four stages, namely planning, observation, action and reflection. The results of the study show that the color of the local clay Bojonegoro can characterize contemporary designs with a blend of colors and materials. The local way of drinking coffee as an inspiration for ‘kothok’ coffee teapots set has the potential to commercialize products and new experiences in drinking coffee.Key words: teapot, pottery, contemporary, Bojonegoro